2016
DOI: 10.2108/zs150209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Olfactory Learning in Crickets

Abstract: Caffeine is a plant-derived alkaloid that is generally known as a central nervous system (CNS) stimulant. In order to examine the effects of caffeine on higher CNS functions in insects, we used an appetitive olfactory learning paradigm for the cricket Gryllus bimaculatus. Crickets can form significant long-term memories (LTMs) after repetitive training sessions, during which they associate a conditioned stimulus (CS: odor) with an unconditioned stimulus (US: reward). Administration of hemolymphal injections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…They also exhibit excellent capability to learn color and pattern of visual targets (Unoki et al, 2006 ; Nakatani et al, 2009 ; Matsumoto et al, 2013b ). Second, applications of pharmacological studies (Unoki et al, 2005 , 2006 ; Matsumoto et al, 2006 , 2016 ; Matsumoto Y. et al, 2009 ; Mizunami et al, 2014 ; Sugimachi et al, 2016 ), gene knockdown by RNA interference (RNAi; Takahashi et al, 2009 ; Awata et al, 2016 ), and genome editing by the CRISPR/Cas9 system (Awata et al, 2015 ) are feasible, thereby greatly facilitating the analysis of molecular basis of learning and memory. Indeed, it can be stated that crickets are one of the best insect models for pharmacological analysis of learning and memory (Mizunami et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also exhibit excellent capability to learn color and pattern of visual targets (Unoki et al, 2006 ; Nakatani et al, 2009 ; Matsumoto et al, 2013b ). Second, applications of pharmacological studies (Unoki et al, 2005 , 2006 ; Matsumoto et al, 2006 , 2016 ; Matsumoto Y. et al, 2009 ; Mizunami et al, 2014 ; Sugimachi et al, 2016 ), gene knockdown by RNA interference (RNAi; Takahashi et al, 2009 ; Awata et al, 2016 ), and genome editing by the CRISPR/Cas9 system (Awata et al, 2015 ) are feasible, thereby greatly facilitating the analysis of molecular basis of learning and memory. Indeed, it can be stated that crickets are one of the best insect models for pharmacological analysis of learning and memory (Mizunami et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, our findings suggested that factors contributing to anatabine-associated reduction of GPCR cascades included a wide range of cyclic nucleotide phosphodiesterases (PDEs) —including several subtypes of PDE1, PDE3, PDE4, PDE7, PDE8, and PDE10—which modulate the intracellular concentrations of cAMP and cyclic guanosine monophosphate (cGMP) by regulating their rates of degradation [ 67 ]. In this regard, several naturally occurring alkaloids, such as caffeine and tolafentrine, also inhibit PDE activities [ 68 , 69 ]. The opium alkaloid papaverine has been identified as a potent and specific inhibitor of PDE10A, with the ability to trigger cAMP and cGMP accumulation as well as CREB phosphorylation in several animal behavioral models [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…G. bimaculatus has also been shown to have good olfactory memory, with some associations being remembered for at least six weeks (Matsumoto and Mizunami 2002). Other work on memory in G. bimaculatus has shown that caffeine can improve long-term memory in this species (Sugimachi et al 2016).…”
Section: Introductionmentioning
confidence: 98%